Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pntd.0008203
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-specific detection of dengue viruses in a nonstructural protein 1-based enzyme-linked immunosorbent assay validated with a multi-national cohort

Abstract: Background Dengue virus (DENV) infections pose one of the largest global barriers to human health. The four serotypes (DENV 1-4) present different symptoms and influence immune response to subsequent DENV infections, rendering surveillance, risk assessments, and disease control particularly challenging. Early diagnosis and appropriate clinical management is critical and can be achieved by detecting DENV nonstructural protein 1 (NS1) in serum during the acute phase. However, few NS1-based tests have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…The prevalence of these amino acid sequence differences in various geographical areas should also be determined. Previous studies showed variations in sensitivity and specificity depending on the collection date after the onset of illness, viral characteristics, and heterotypic DENV infection in NS1 DENV-specific detection using clinical specimens [ 40 , 41 , 42 , 43 , 44 ]. These factors might have also played a role in the cross-reactivity observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of these amino acid sequence differences in various geographical areas should also be determined. Previous studies showed variations in sensitivity and specificity depending on the collection date after the onset of illness, viral characteristics, and heterotypic DENV infection in NS1 DENV-specific detection using clinical specimens [ 40 , 41 , 42 , 43 , 44 ]. These factors might have also played a role in the cross-reactivity observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…using Cytofix from BD Biosciences and subsequently washed twice in DPBS 2% FBS. Replicates of cells were fixed and stained with anti-NS1 antibodies 7724.323 (diluted 1:1,000 anti-dengue NS1 mAb 323) and 7944.644 (diluted 1:2,000; anti-Zika NS1 mAb 644) 36,37 , obtained from Lee Gehrke. Other replicates of cells were run on a CytoFLEX LX flow cytometer or used for a nanoluciferase assay using Nano-Glo from Promega, according to the manufacturer's instructions, and measured using a BioTek Synergy H1 plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…[57,58] There exist four different DENV serotypes that are difficult to distinguish except NAAT reactions or ELISA assays involving costly antibodies. [59] Moreover, cross-infection with different serotypes has also been linked with severe dengue. [57] Therefore, an ultrasensitive NAAT assay that can be carried out at near ambient temperature without using real-time PCR would be invaluable towards sequencespecific detection of DENV serotypes at limited-resource settings.…”
Section: Validation Of Redox Probe and Naat Detection With Electroche...mentioning
confidence: 99%